Pengaruh CAR, NPL, LDR dan BOPO terhadap Return ON Assets (ROA) pada Bank yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 - Panji Maulana; Sany Dwita; Nayang Helmayunita (Universitas Negeri Padang, 2021)
This research aims to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Peforming Loan (NPL), dan Operational Effeciency Ratio (OER) of commercial banks listed on the Indonesia Stock Exchange 2017-2019. Population in this research while sample was defined bu purposive sampling method and 28 Banks as sample. Type of data that we used was secondary data (panel data) from www.idx.com and company's website. Data collection method used documentation method and multiple regression analysist method. The result are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) have no effect on ROA.